The Physical Setting of Street Food on Jalan Darussalam, Lhokseumawe City. - Samirah, Fathya; Novianti, Yenny; Muliana, Erna (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2025)
The Spatial Configuration of Street Food on Jalan Darussalam, Banda Sakti District, Lhokseumawe City: A Qualitative Study The street food corridor of Jalan Darussalam, located in Banda Sakti District, Lhokseumawe City, is one of the main roads with a strategic role in the activities of the local community. This road serves as a hub for economic and social activities, featuring various businesses such as shops, stalls, and street food vendors lining its sides.The purpose of this study is to identify the factors influencing the spatial physical setting of street food establishments in the urban space of Jalan Darussalam, Banda Sakti District, Lhokseumawe City. Through field observations and interviews with street food vendors, consumers, and local residents, the study reveals that adequate infrastructure enhances the attractiveness of the street food area, increases vendors’ incomes, and supports food security and community welfare. This study employs a qualitative method with a behavior mapping approach. The findings highlight spatial variables such as location, distance, proximity, adjacency, and territoriality. Street food tends to concentrate in strategic locations with high accessibility, such as city centers, market areas, and major transportation routes. The spatial patterns, including the distance between vendors and their proximity to supporting facilities like terminals, offices, and residential areas, form a spatial network that contributes to economic and social activities. The adjacency of vendors creates clusters that serve as an added attraction for consumers. From a territorial perspective, street food connects various urban space functions but also has the potential to generate conflicts over space usage, particularly in densely populated areas.